Відносний знос переривчастих шліфувальних кругів з надтвердих матеріалів - Якимов, А. А.; Бовнегра, Л. В.; Уминський, С.; Тонконогий, В. М.; Смірнова, Ю. (Національний технічний університет "Харківський політехнічний інститут", 2020)
При шліфуванні кругами, робоча поверхня яких складається з періодичних виступів і западин, в пружній системі верстата через переривчастість процесу різання виникають високочастотні коливання малої амплітуди, які полегшують процес стружкоутворення і сприяють формуванню на крузі розвиненого різального мікрорельєфу. Однак при певних співвідношеннях довжин різальних виступів і западин і при певних їх кількостях може виникнути параметричний резонанс, передумовою якого є періодична зміна в часі жорсткості пружної системи верстата. Параметричний резонанс негативно позначається не тільки на питомому зносі алмазного круга, а й на якості обробляємої поверхні. Це передбачає необхідність подальшого пошуку нових досліджень впливу параметричного резонансу, що виникає при переривчастому шліфуванні на відносну витрата алмазних кругів. У статті розрахунковим і експериментальним шляхами виявлено екстремальний характер залежностей питомого зносу переривчастих кругів з надтвердих матеріалів від кількості прорізів на робочій поверхні інструменту і від величини відношення протяжності западини до довжини ріжучого виступу круга. Також розрахунково-експериментальним шляхом виявлено характери впливу розмірів і кількості конструктивних елементів, з яких утворено робочу поверхню алмазних переривчастих кругів, а також жорсткості різання на параметричну стійкість пружної системи плоскошліфувального верстата.

When grinding circles, the working surface of which consists of periodically protrusions and depressions, in the elastic system of the machine due to the interruption of the cutting process there are high-frequency oscillations of small amplitude, which facilitate the process of chip formation and contribute to the formation of a developed cutting microrelief. However, at certain ratios of lengths of the cutting projections and depressions and at certain their quantities, parametric resonance may occur, which is a prerequisite for a periodic change in the stiffness time of the elastic system of the machine. Parametric resonance has a negative effect not only on the specific wear of the diamond kkol, but also on the quality of the machined surface. This implies the need for further exploration of the effect of parametric resonance arising from intermittent grinding on the relative flow of diamond circles. In the article, using the calculated and experimental ways, identified The extreme nature of the dependences of the specific wear of discontinuous circles of superhard materials on the number of slots on the working surface of the tool and on the ratio of the extent of the cavity to the length of the cutting ridge of the circle. Also, using the computational and experimental ways the characters of the influence of the dimensions and number of structural elements from which the working surface of diamond discontinuous circles was formed, as well as the rigidity of cutting on the parametric stability of the elastic system of a surface grinding machine, were revealed. The nature of the influence of the size and number of structural elements from which the working surface of diamond discontinuous wheels is formed, as well as the cutting rigidity on the parametric stability of the elastic system of the surface grinding machine is revealed by calculation and experiment.
Warning warning of performance grinding wheels of extractive materials
Keywords: робоча поверхня круга; різальний виступ; working surface of the wheels; cutting protrusion